Pediatric Hand Surgery Training in Nicaragua: A Sustainable Model of Surgical Education in a Resource-Poor Environment - Manske, Mary Claire B.; Rios Roque, Jairo J.; Zelaya, Gabriel Ramos; James, Michelle A. (Frontiers in Public Health, 2017)
Recent reports have demonstrated that nearly two-thirds of the world’s population do not have access to adequate surgical care, a burden that is borne disproportionately by residents of resource-poor countries. Although the reasons for limited access to surgical care are complex and multi-factorial, among the most substantial barriers is the lack of trained surgical providers. This is particularly true in surgical subspecialties that focus on life-improving, rather than life-saving, treatments, such as pediatric hand and upper extremity surgery, which manages such conditions as congenital malformations, trauma and post-traumatic deformities including burns, and neuromuscular conditions (brachial plexus birth palsy, spinal cord injury, and cerebral palsy). Many models of providing surgical care in resource-limited environments have been described and implemented, but few result in sustainable models of health care delivery. We present our experience developing a pediatric hand and upper extremity surgery training program in Nicaragua, a resource-limited nation, that grew out of a collaboration of American and Nicaraguan orthopedic surgeons. We compare this experience to that of surgeons undergoing subspecialty training in pediatric upper limb surgery in the United States, highlighting the similarities and differences of these training programs. Finally, we assess the results of this training program and identify areas for further growth and development.